Para vivir mañana todavía: Reconfiguraciones de la mirada y la memoria en el proceso de creación presencial y virtual de Aliento y Vacío. - Medina Hú, Lucero (2022)
The collective creation in performing arts presents new challenges in virtuality. Intermedials creations propose the reorganization of the creative processes, of the body and the gaze of the performing artists. Based on the situated experience of Aliento y vacío, short film, whose process continued in a virtual and individual way due to the pandemic, we analyze the relationships that are established between the performing artist and his creative material in virtuality, taking as references concepts such as body memory, the rewriting of materials and collective weaving. At a methodological level, this work has involved reviewing the documentary material of the research process and conducting interviews with the performing artists. Part of the proposal incorporates the conversations between the authors as devices to generate a co-perception of the experience we analyze as well as the writing process.